Entrepreneurial Profiles at the University: A Competence Approach - Martínez-Martínez, Sofía Louise; Ventura, Rafael (Frontiers in Psychology, 2020)
The Entrepreneurial University plays a central role in entrepreneurial ecosystems and actively influences the development of entrepreneurial human capital, which is a critical asset for many economies. There is thus a requirement for the identification and strengthening of entrepreneurial competences, but no previous studies have included any analysis of these competences in the university context using an approach based on profiles. The present study fills this gap by investigating the existence of different entrepreneurial profiles among students, based on their competences. It also defines key competences that are critical for differentiating between these profiles and improving entrepreneurial competence levels more generally. To meet these objectives, a field research campaign was developed. Data on 1104 students from various degrees and faculties were collected and analyzed using a quantitative methodological approach. The results reveal the existence of four entrepreneurial competence profiles, namely low profile, top profile, social profile, and grit profile. Among as many as 12 possible entrepreneurial competences, the most prominent can explain to a large extent the entrepreneurial profiles of students; these are networking and professional social skills, community engagement, perseverance of effort, and consistency of interest. The results provide evidence of the importance of social capital and grit. In addition to their contribution to the theory in this area and the development of the Entrepreneurial University paradigm, the results are also useful for the design of training strategies aimed at strengthening the levels of competence of students, thereby providing universities with tools to foster the creation of entrepreneurial human capital.